Normal Dual Isotope V/Q SPECT Model for Monte-Carlo Studies - Bourhis, David; Wagner, Laura; Essayan, Marine; Robin, Philippe; Le Pennec, Romain; Salaun, Pierre Yves; Le Roux, Pierre Yves (Frontiers in Medicine, 2020)
Background There is currently no reliable or validated tool to delineate and quantify functional lung volumes with ventilation/perfusion (V/Q) SPECT/CT. The main challenges encountered include the physiological non-uniformity of lung function, such as the anterior-to-posterior gradient on perfusion images, and the lack of ground truth to assess the accuracy of delineation algorithms. In that respect, Monte-Carlo simulations would be an interesting tool. Thus, the aim of this study was to develop a realistic model of dual-isotope lung V/Q SPECT-CT Monte-Carlo simulations, integrating the anterior to posterior gradient on perfusion. Methods Acquisitions and simulations parameters were set in accordance to nuclear medicine guidelines for V/Q lung SPECT-CT. Projections were acquired and simulated, then the reconstructions (with and without attenuation correction (AC)) were compared. A model was built from a patient’s CT scan. To model the anterior to posterior gradient, the lungs were divided into sixteen coronal planes, where a rising radioactivity concentration was set. To assess the realism of simulations, they were compared to a normal co-registered normal cases database in terms of pixelwize Z-score map. Results For ventilation images, mean (SD) Zscores on Zscore maps were -0.2 (0.7) and -0.2 (0.7) for AC and noAC images, respectively. For perfusion images, mean (SD) Zscores were -0.2(0.6) and -0.1 (0.6) for AC and noAC images, respectively. Conclusion We developed a model for dual isotopes lung V/Q SPECT-CT, integrating the anterior-to-posterior gradient on perfusion images. This model could be used to build a catalog of clinical scenarios, in order to test delineation methods of functional lung volumes.